2021
DOI: 10.1177/17455065211046139
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of preconception care and associated factors among maternal health care providers working in urban public health institutions of Eastern Ethiopia

Abstract: Background: Provision of preconception care is significantly affected by the health care provider’s knowledge of preconception care. In Ethiopia, preconception care is rare, if even available, as part of maternal health care services. Thus, this study aimed to determine the level of knowledge of preconception care and associated factors among health care providers working in public health facilities in Eastern Ethiopia. Methods: A multicenter cross-sectional study was conducted from 1 March to 1 April 2020. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
2
4
1
Order By: Relevance
“…This was attributed to unavailability of provision of preconception care guidelines and standards. The findings are similar to those in a study conducted by Sori et al [16] in Eastern Ethiopia, where 85.1% of the respondents reported that there were no precon-ception care guidelines in their institution. Due to non-availability of preconception care standards and guidelines at Ndola Teaching Hospital, service provision was being done in a disorderly manner.…”
Section: Provision Of Preconception Of Caresupporting
confidence: 89%
“…This was attributed to unavailability of provision of preconception care guidelines and standards. The findings are similar to those in a study conducted by Sori et al [16] in Eastern Ethiopia, where 85.1% of the respondents reported that there were no precon-ception care guidelines in their institution. Due to non-availability of preconception care standards and guidelines at Ndola Teaching Hospital, service provision was being done in a disorderly manner.…”
Section: Provision Of Preconception Of Caresupporting
confidence: 89%
“…Nevertheless, the rapid training intervention increased the level of knowledge of the health providers similar to results observed in studies conducted in the USA with health care students and residents [ 13 , 15 ]. As insufficient training is reported to negatively impact the confidence and ability of a health care provider to provide preconception care [ 5 , 6 , 35 , 36 ], our result resonates with others that highlight the need for specific and continuous in-work trainings that may allow updates in preconception care-related topics to optimize its provision [ 29 ].…”
Section: Discussionsupporting
confidence: 73%
“…Health providers in both the intervention and control groups showed considerable knowledge of preconception care before the intervention. Comparing our results with others, it was observed that the knowledge of health providers in our study was even higher than that observed in either high-income countries or other middle-income countries [ 7 , 9 , [25] , [26] , [27] , [28] , [29] ].…”
Section: Discussioncontrasting
confidence: 50%
“…The causative factor is the low awareness of the use of pre-pregnancy care (Du et al, 2021). This condition is supported by low knowledge (Wegene et al, 2022), unsupportive attitude (Okemo et al, 2021), high financing so they do not have access to services (Mazza et al, 2013), not having enough time (Habte et al, 2021), and lack of socialization about the use of preconception treatments (Sori et al, 2021). Another cause that is the main reason for the low utilization of pre-pregnancy services is unplanned pregnancies (Du et…”
Section: Discussionmentioning
confidence: 99%